Towards high value markets: a case study of smallholder vegetable farmers in Indonesia - Maspaitella M; Garnevska E; Siddique MI; Shadbolt N (International Food and Agribusiness Management Association)
The expansion of modern markets has significant implications for agriculture in many developing countries that provides both opportunities and challenges for smallholder farmers. The purpose of this paper is to analyse key determinants affecting farmers’ participation in high value markets, compared to traditional market. Face to face interviews based on a questionnaire were conducted with a sample of 126 smallholder vegetable farmers in the Manokwari region. Binary logistic regression and bivariate correlation analysis were used in this study. The results suggested that age, education level, vegetables cultivated area and membership in farmer groups/cooperatives were the key determinants that had significant effects on the smallholder farmers’ decision about marketing channel participation. In addition, the income generated from vegetable farming was positively correlated to high value market participation. Some implications that need to be prioritized in agricultural development strategies include improving technical innovations and empowering collective actions through cooperatives or farmer groups.
Keywords: Indonesia; high value market; market channel decisions; traditional market; vegetable farmers; 0701 Agriculture, Land and Farm Management